Some Abortifacient Plants Used by the Tribal People of Andhra Pradesh, India - M. Venkaiah, P. Prayaga Murty* and (Journal of Phytology, 2010)
Plants have been used by women since the beginning of time in an attempt to control their fertility. The information was passed from mother to daughter and generation to generation. The use of abortifacient plants is a common practice among the interior tribal people of Andhra Pradesh. In the present study a list of 33 plant species belonging to29 genera and 26 families are used as abortifacient. The study was conducted among the 33 tribal groups of Andhra Pradesh. The mode of preparation, administration and the dosage of the drugs use are collected from the tribal doctors and lady tribal doctors to terminate the early stage of pregnancy.